Campo de Escuta: Procedimento composicional com camadas sonoras em loop - Tavares, Pedro Henrique Carneiro (2016)
In this work we developed a compositional procedure that employs independent sound layers forming loops, whose interaction becomes determinant of the formal design. Such procedure, called Listening Field, was metaphorically inspired on planetary orbits. Four compositions were written in order to demonstrate the procedure: Disco de Acreção, Delta Orionis, and Nemesis, for string octet; and Sistema Solar for string orchestra. A few tangential subjects are approached in this work, including periodicity, relationship between "listening" and "non listening", silence, and the influence of cultural background on the listener's perception.